Análise dos efeitos do ensino profissionalizante sobre o abandono escolar no ensino médio - Terceiro, Gláucia Maria Almeida (2019)
The Brazilian public education system suffers from dysfunctionalities that become more vulnerable to its students. The problem is particularly acute and persistent at the middle level, where young people face a shift to the labor market. The principal is missing from the high school in the students are shared and high rates of school failure. How was carried out this year in 2016 a curricular reform of high school, which was inspired by the experience with education in various state networks. This study is the study of the evaluation of the teaching of the high schools in the results. Therefore, it was verified that schools migrated from regular education to vocational education between 2007 and 2015, comparing them with the objective of only regular education. A combination of the differences method was applied in relation to the propensity score pairing, in order to mitigate the sample selection potential. The results show that, like those observed, the schools that migrated to vocational education reduced the dropout rate in high school by about 0.5 percentage points.